The Principle of Primary Consideration of the Best Interests of the Child in Civil Procedure in Ukraine - Fursa Yaroslavivna Svitlana; Bordiuh Oleksandrivna Tetiana; Fursa Yevhenovych Yevhen (LeXonomica, 2022)
The article examines approaches to understanding the terms "children’s interests" and "the best interests of children" in scientific theory and law enforcement practice in Ukraine. The authors summarise the experience of Ukrainian judicial practice in observing the principle of primary consideration and ensuring the best interests of the child. This experience is being studied on the example of resolving civil cases on determining the place of residence of a child for the most part. The authors make suggestions concerning the application of Article 3 of the UN Convention on the Rights of the Child. The authors propose to understand the principle of primary consideration and ensuring the best interests of children as the use of the best possible ways and means of resolving cases with the participation of children, which would meet their contemporary interests, consider their existing needs along with the perspectives for the future to the greatest extent possible. Povzetek. V članku so obravnavani pristopi k razumevanju pojmov "interesi otrok" in "največja korist otrok" v znanstveni teoriji in praksi kazenskega pregona v Ukrajini. Avtorji povzemajo izkušnje ukrajinske sodne prakse pri spoštovanju načela primarnega upoštevanja in zagotavljanju otrokovih koristi. Te izkušnje so proučene na primeru reševanja civilnih zadev o določitvi otrokovega prebivališča v pretežnem delu. Avtorji podajajo predloge v zvezi z uporabo 3. člena Konvencije ZN o otrokovih pravicah. Avtorji predlagajo, da se načelo prednostnega upoštevanja in zagotavljanja otrokovih koristi razume kot uporaba najboljših možnih načinov in sredstev reševanja zadev ob sodelovanju otrok, ki bi v največji možni meri ustrezali njihovim sodobnim interesom, upoštevali njihove obstoječe potrebe skupaj s perspektivami za prihodnost.